Socks Studio and the Digital through the Lens of architectural Discipline. Talks with Mariabruna Fabrizi and Fosco Lucarelli - Irene Di Pietro (Museum, Materials and Discussions)
In light of the first MMD's issue, the column dedicated to digital for museums presents an essay about Socks: the web project conceived by Mariabruna Fabrizi and Fosco Lucarlli. Socks was created as a digital archive and currently represents a web platform capable of combining research and architectural practice with original contributions by its authors.